Pengaruh detoksifikasi dan konsentrasi substrat terhadap produksi biohidrogen dari hirolisat ampas tahu - Amir Husin; Sarto Sarto; Siti Syamsiah; Imam Prasetyo (Jurnal Rekayasa Proses, 2014)
The effect of detoxification and substrate concentration on fermentative hydrogen production by mixed cultures was investigated in batch experiments using tofu solid waste (TSW) hydrolysate as substrate. TSW as the by product of tofu processing industry was hydrolyzed using diluted hydrochloric acids as catalyst (0.5% wt HCl, 104°C and 30 minutes). After neutralized by Ca(OH)2 (aq) and then treated by activated carbon for one hour, the hydrolysate was used for biohydrogen production. The experimental results show that, during fermentative hydrogen production under mesophilic condition and initial pH 6.5 were influenced both substrates without/with detoxification. The maximal hydrogen yield of 4.9 mmol/g reducing sugar (RS) were obtained at detoxified substrate consentration of 2 g GT/L. Detoxification has also shown to shortened lag phase of fermentation (l). Adaptation time of microbes during fermentation was reduced from 20 into 13.25 hours for fermentation without/with detoxification respectively at initial substrate concentration of 2 g GT/L.